Kewarganegaraan dan Perlindungan Hukum Terhadap Minoritas - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Fadli Muhsin Setiawan; Lailatun Hasna; Nanda Nurmayanti (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study compares national and Islamic law on citizenship and legal protection for minority groups. Citizenship determines the basic rights of individuals, while minority groups often face discrimination in national and Islamic legal systems. This research explores the protection of minorities in international human rights-based national law and Islamic law through the concept of ahl al-dhimma. Case studies from India, France, Saudi Arabia and Tunisia show a variety of approaches, such as the controversial CAA in India, the laïcité principle in France, and conservative and progressive interpretations of Islamic law in Saudi Arabia and Tunisia. The results highlight the challenges of implementing equal protection in both legal systems due to political and social dynamics. In conclusion, inclusive policies based on interfaith and cross-cultural dialogue are needed to strengthen minority rights globally.